Implikasi Keterlambatan Berulang Terhadap Integritas Akademik dan Etos Belajar Mahasiswa - Thesa Lorika Casanova Purba; Mila Lumbangaol; Denrio Tambunan; Mael Steven Sihombing (Dewantara : Jurnal Pendidikan Sosial Humaniora, 2025)
Repeated lateness in higher education is often regarded as a minor habit, even though it has serious implications for students’ academic integrity and learning ethic. This study aims to analyze the effect of repeated lateness on academic integrity and students’ learning ethic. A mixed-methods approach was employed, consisting of quantitative and qualitative stages. Quantitative data were collected through questionnaires measuring the frequency of lateness, time management, learning motivation, and academic integrity. Qualitative data were obtained through in-depth interviews and focus group discussions with students and lecturers. The findings reveal a significant negative relationship between the frequency of lateness and students’ learning ethic. Students who are frequently late tend to show lower learning motivation, minimal classroom engagement, and weaker study consistency. Repeated lateness is also associated with a decline in academic integrity, reflected in neglecting deadlines, low responsibility in group work, and a growing tendency to seek instant solutions in learning. The causes of repeated lateness are influenced by internal factors, such as poor time management and low motivation, as well as external factors, including part-time work and transportation conditions. This study emphasizes the importance of institutional policies to promote a culture of punctuality in order to strengthen academic integrity and students’ learning ethic.